2020
DOI: 10.1002/brb3.2003
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the anterior cingulate cortex in Crohn’s disease: A neuroimaging perspective

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 80 publications
1
12
0
Order By: Relevance
“…For example, Wang and colleagues found that gut microbiota alteration impaired DMN topological properties (including clustering coefficient, local efficiency, Gamma , and Sigma ) by increasing systemic inflammation in end-stage renal disease patients ( Wang et al, 2019 ). Certainly, the occurrence of some diseases is closely correlated with gut microbial alteration, and these diseases show changes in topological parameters of the functional network at the same time, which might provide indirect evidence that gut microbiota can influence the topological properties of functional networks, such as in IBS ( Kano et al, 2020 ) and Crohn’s disease ( Kong N. et al, 2021 ). In this study, we found that some nodal properties of the brain functional network were related to the diversity and enterotypes of the gut microbiota in healthy young adults.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Wang and colleagues found that gut microbiota alteration impaired DMN topological properties (including clustering coefficient, local efficiency, Gamma , and Sigma ) by increasing systemic inflammation in end-stage renal disease patients ( Wang et al, 2019 ). Certainly, the occurrence of some diseases is closely correlated with gut microbial alteration, and these diseases show changes in topological parameters of the functional network at the same time, which might provide indirect evidence that gut microbiota can influence the topological properties of functional networks, such as in IBS ( Kano et al, 2020 ) and Crohn’s disease ( Kong N. et al, 2021 ). In this study, we found that some nodal properties of the brain functional network were related to the diversity and enterotypes of the gut microbiota in healthy young adults.…”
Section: Discussionmentioning
confidence: 99%
“…Recent MR spectroscopy study showed that patients with CD experiencing abdominal pain have an imbalance in glutamate and γ‐aminobutyric acid levels in the anterior cingulate cortex, whereas another CD study showed that lower grey matter volumes in the anterior cingulate cortex correlated strongly with higher pain scores 76 . In terms of function, connectivity within the default mode network was increased in the anterior cingulate cortex and decreased between the anterior cingulate cortex and amygdala, which may be attributed to negative emotions and changes in gut microbiota 77 . Collectively, multidimensional brain MRI data suggest that the anterior cingulate cortex is associated with pain and depression in patients with CD, indicating that the anterior cingulate cortex might be a potential neural alternative for managing the progression of CD.…”
Section: Role Of Brain Mr Imaging In Gut‐brain Axis Research In CDmentioning
confidence: 99%
“… 76 In terms of function, connectivity within the default mode network was increased in the anterior cingulate cortex and decreased between the anterior cingulate cortex and amygdala, which may be attributed to negative emotions and changes in gut microbiota. 77 Collectively, multidimensional brain MRI data suggest that the anterior cingulate cortex is associated with pain and depression in patients with CD, indicating that the anterior cingulate cortex might be a potential neural alternative for managing the progression of CD.…”
Section: Role Of Brain Mr Imaging In Gut‐brain Axis Research In CDmentioning
confidence: 99%
“…Interestingly, the anterior cingulate cortex (ACC), part of the autonomic forebrain loop, functioning as a relay hub and transmitting various input signals after evaluating requirements from other regions to guide adaptive behaviors, is particularly sensitive to cytokines ( 158 , 159 ). Notably, both depression and CD are inflammation-related disorders and dysfunction of the ACC was reported in depression and CD ( 160 , 161 ). Further, a recent study from Xu group found that patients with CD who were in the active phase exhibited higher amplitude of low frequency fluctuation (ALFF) in the left ACC and a positive correlation between mWavelet-ALFF values of the ACC and Hospital Anxiety and Depression Scale-depression scores in CD patients ( 162 ).…”
Section: Vagal Tone Gut Permeability and Inflammation And Depressionmentioning
confidence: 99%